DOP38 An observational study to evaluate the burden of illness in patients with Crohn's Disease with and without perianal fistulas in the USA. (27th May 2021) - Jiang, J; Cazzetta, S E; Athavale, A; Kuharic, M; Fan, T; Silber, A; Vijay, A; Hadker, N; Sharpe, E; Nazarey, P P
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory condition of the gastrointestinal tract that can lead to complications such as perianal fistulas (PAFs). This study compared disease burden, experiences and health-related quality of life between patients who have CD with PAFs (CPF) and those who have CD without PAFs (non-PAF CD). Methods: This cross-sectional, observational study was conducted in three cohorts of US patients aged 18–89 years with self-reported physician-diagnosed CD: (1) non-PAF CD; (2) CPF without PAF-related surgery; and (3) CPF with PAF-related surgery. Data on medical and surgical interventions, CD-specific symptoms and Fecal Incontinence Quality of Life (FIQL) were collected via a web-enabled questionnaire. Statistical comparisons were assessed at the 0.05 level. Results: The mean (standard deviation) age of patients in cohorts 1 (n = 300), 2 (n = 51) and 3 (n = 52) was 47 (16.4), 40 (12.2) and 39 (13.1) years, respectively. In patients with CPF (cohort 2 + 3), 59 (57%) reported multiple fistulas and 48 (47%) reported fistula recurrence/persistence. Compared with cohort 1 (non-PAF CD), more patients with CPF reported currently receiving biologic treatment or immunomodulators for CD (58% vs 43% and 23% vs 15%, respectively; both p = 0.01). More patients with CPF also reported undergoing ≥ 1 CD-related surgery and experiencing ≥ 1 failures of CD-related surgery (79% and 20%, respectively) versus cohort 1 (53% and 9%, respectively; both p < 0.001). In cohort 3, 63% of patients had ≥ 3 PAF-related surgeries, and in those receiving seton placement (n = 37), 8% reported placement failure. Post-surgical/seton placement complications were common; the most frequently reported were worsening of pain and swelling around the anus (33%) and fever/infection (29%). CD-specific symptom frequency and severity results indicated a high symptom burden across cohorts; fatigue was reported with the highest frequency and severity. Faecal incontinence (FI) and leakage-related symptoms affected greater proportions of patients in cohorts 2 and 3, often with greater severity and frequency, compared with cohort 1 (Fig.1). Across all cohorts, 58% of patients (cohort 1/2/3, n = 158/35/40) reported experiencing FI and completed the FIQL questionnaire: cohorts 2 and 3 reported lower (worse) FIQL scores across domains than cohort 1 (Fig.2). Conclusion: The burden of illness in patients with CPF is substantial, with medical and surgical intervention rates, and symptom severity and frequency greater than for those with non-PAF CD. Higher disease burden, including FI, was noted in patients with CPF compared with the non-PAF CD cohort. An unmet need remains for improved management and outcomes of CPF. Sponsor: Takeda Pharmaceuticals USA, Inc.